TRANSFORMING HEALTHCARE: CLOUD TECHNOLOGIES AND AI IN PATIENT CARE - Srikanth Padakanti (INTERNATIONAL JOURNAL OF ENGINEERING AND TECHNOLOGY RESEARCH (IJETR), 2024)
This comprehensive article explores the transformative impact of cloud technologies and artificial intelligence (AI) on the healthcare sector, focusing on their synergistic effects in enhancing patient care and operational efficiency. It examines the fundamental aspects of cloud computing in healthcare, including its definition, key features, and benefits in patient data management, with particular emphasis on cloud-based Electronic Health Record (EHR) systems. The article delves into the multifaceted applications of AI in healthcare, discussing its role in predictive analytics and the development of AI-driven diagnostic tools. Through a series of case studies, the article illustrates the real-world implementation of these technologies, highlighting both the challenges faced and the benefits realized in large-scale hospital networks, cancer detection, and telemedicine platforms during the COVID-19 pandemic. The impact of these innovations on healthcare outcomes and operations is thoroughly analyzed, demonstrating improvements in patient outcomes, cost reduction, and administrative efficiency. The article also addresses critical challenges, including data privacy concerns, regulatory compliance, and integration issues with existing healthcare systems. Finally, it explores future trends and potential advancements in the field, providing a forward-looking perspective on the continued evolution of healthcare technology. This comprehensive overview offers valuable insights for healthcare professionals, policymakers, and researchers seeking to understand and leverage the potential of cloud and AI technologies in transforming healthcare delivery and outcomes